2004
DOI: 10.1007/s00432-003-0526-7
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human erythropoietin attenuates weight loss in a murine cancer cachexia model

Abstract: Anaerobic glycolysis in a growing C26-B tumor is related to weight loss. RhEPO administration results in a reduction of the percentage weight loss; this effect is probably mediated by an increased hemoglobin concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…The definition of the C26 tumor as adenocarcinoma is a major mistake in terminology [10,12,35]. We have confirmed that the C26 cells, originally obtained from a colon carcinoma, when ectopically implanted in mice form an undifferentiated carcinoma, which should thus be referred to as such.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The definition of the C26 tumor as adenocarcinoma is a major mistake in terminology [10,12,35]. We have confirmed that the C26 cells, originally obtained from a colon carcinoma, when ectopically implanted in mice form an undifferentiated carcinoma, which should thus be referred to as such.…”
Section: Discussionsupporting
confidence: 68%
“…Myostatin negatively regulates skeletal muscle mass, though inhibition of its downstream pathways does not attenuate C26-induced cachexia, thereby suggesting that myostatin does not play a role in this context [39]. Anaerobic glycolysis in a C26 tumor is related to weight loss, while erythropoietin administration has been shown to reduce weight loss [12]. Accordingly, exercise training attenuates C26-induced muscle wasting [40].…”
Section: Introductionmentioning
confidence: 99%
“…Others explored rHuEpo in combination with fractionated radiation in a murine cancer cachexia model: They concluded that rHuEpo had a beneficial effect by contributing to radiosensitization and/or reducing weight loss 72, 73. In contrast, no radiosensitizing effect was observed in a rat tumor model with darbepoetin alpha (DA) at a high dose, even though there was an increase in tumor oxygenation 74.…”
Section: Esas In Animal Models Of Tumor Growthmentioning
confidence: 99%
“…Other drugs that are investigated to be used for cancer cachexia include Erythropoetin [171][172][173] , ACE inhibitors [174] , and β-blockers [175] .…”
Section: Othersmentioning
confidence: 99%